Evaluating Foot and Mouth Disease Vaccination Services through Assessment of Beef Cattle Farmers’ Satisfaction in Sleman Regency - Syihabuddin, M. Y.; Andarwati, S.; Guntoro, B.; Putra, A. R. S. (Tropical Animal Science Journal, 2025)
The study aimed to evaluate the satisfaction of beef cattle farmers towards Foot and Mouth Disease (FMD) vaccination services in Sleman Regency. A survey method was employed, involving 120 farmers who participated in the FMD vaccination program. Beef cattle farmers’ satisfaction levels were assessed using the Customer Satisfaction Index (CSI) method, which revealed that 82.25% of farmers were highly satisfied with various indicators of the vaccination services. To identify areas for improvement, the Importance-Performance Analysis (IPA) was utilized. The IPA highlighted several attributes as top priorities for performance enhancement, including: The priority indicators for performance improvement include service procedures that are easy to understand, vaccination officers not discriminating based on farm location, the handling skills of the officers, and the application of biosecurity measures according to procedures. Beef cattle farmers’ perceptions of the benefits of the vaccination program were 83.8%, indicating a rating of ‘very good’. These insights offer a foundation for policymakers to optimize FMD vaccination services, increase beef cattle farmers’ satisfaction, and promote livestock health.